AB0695 Anti-prothrombin/phosphatidyl-serine complex autoantibodies in antiphospholipid syndrome: Preliminary data using a new ELISA method. (23rd January 2014) - Fabris, M.; Mansutti, E.; Quartuccio, L.; Peresan, J.; Curcio, F.; De Vita, S.; Tonutti, E.
Abstract : Background: New emerging anti-phospholipid (aPL) assays could improve our ability in diagnosing anti-phospholipid syndrome (APS). However, the availability of aPL assays in routine laboratory practice is limited and present available assays frequently not so efficient. Objectives: To test the performance of a new immunometric assay for prothrombin/phosphatidylserine IgG and IgM complex autoantibodies (aPT/PS) in routinely attending patients (Autoimmunology Unit, University Hospital of Udine, Italy). Methods: The study included 138 consecutive patients (78% female, age 53±15 years; range 18-88) amongst which 83 with systemic lupus erythematosus (SLE), undifferentiated connective tissue diseases (UCTD) or APS. 52 healthy donors (29F/23M, age 37±13 yrs, range 18-65) were enrolled as controls. From the laboratory point of view, there were 108 lupus anticoagulant (LAC) positive patients (70.4% of which anti-cardiolipin/anti-beta2 glycoprotein I-negative) and 25 LAC/aCL/anti-b2GPI-negative. All the serum samples were analysed for the anti-PT/PS IgG and IgM antibodies using the new ELISA method under development by Inova (San Diego, CA). Fifty-two samples were analysed also for IgG/IgM anti-prothrombin autoantibodies by the routinely used method (Orgentec, Mainz, Germany). Results: Overall, the Inova ELISA test revealed a high prevalence of the anti-PT/PS antibodies amongst LAC positive patients (anti-PT/PS IgG and/or IgM positive in 64/108, 59.3% of LAC-positive patients versus 4/52, 7.7% of controls; p<0.001). This prevalence was in line with that awaited (1). Globally, patients with SLE, UCTD or APS, were 47/83 (56.6%) anti-PT/PS positive. The percentage increased when considering only the LAC-positive cases (39/53, 73.6%). Compared to the routinely used IgG/IgM anti-prothrombin assay, the new anti-PT/PS complex assay confirmed 5/8, 62.5% of the positive samples, but was able to identify another 24 (46.1% of the 52 cases analysed with both assays) new positive cases, who were all SLE/UCTD/APS patients. Conclusions: As reviewed by Amengual et al (1), the antibodies more closely associated with APS and LAC are directed to the complex between PT and anionic phospholipid (such as PT/PS) rather than PT alone. The new anti-PT/PS complex antibodies assay by Inova improves the capability to identify such reactivity and may help to better characterize patients with APS. References: Amengual O. et al, Arthritis & Rheum 2003. Disclosure of Interest: None Declared